2011
DOI: 10.3109/14767058.2010.501120
|View full text |Cite
|
Sign up to set email alerts
|

Severe fetal valproate syndrome: combination of complex cardiac defect, multicystic dysplastic kidney, and trigonocephaly

Abstract: Valproic acid (VPA) is a teratogenic drug used in pregnant women for the treatment of epilepsy and mood disorders. Fetal valproate syndrome (FVS) is characterized by a number of abnormalities associated with VPA exposure in utero including neural tube defects, congenital heart defects, limb defects, genitourinary defects, brain, eye and respiratory anomalies, and abdominal wall defects. Complex cardiac defect and trigonocephaly have rarely been reported and multicystic dysplastic kidney has never been detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…8 The characteristic facial anomalies include arched eye brows, epicanthal folds, broad nasal bridge, small nose with anterverted nostrils and occasionally cleft palate and trigonencephaly due to premature closure of the metopic suture. 1,5 The most characteristic facial findings are small nose (57%) and epicanthal folds (31%). Limb anomalies are characteristically preaxial in the upper extremity and include absent radius and hypoplastic, bifid or triphalangeal thumbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The characteristic facial anomalies include arched eye brows, epicanthal folds, broad nasal bridge, small nose with anterverted nostrils and occasionally cleft palate and trigonencephaly due to premature closure of the metopic suture. 1,5 The most characteristic facial findings are small nose (57%) and epicanthal folds (31%). Limb anomalies are characteristically preaxial in the upper extremity and include absent radius and hypoplastic, bifid or triphalangeal thumbs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk of neural tube defects with intrauterine exposure to valproate is 10 times than that compared with the general population 4 and the risk for facial, cardiac, genitourinary and skeletal anomalies is 2 to 5 times than that compared with the general population. 5 The inhibition of histone deacetylase and changes in gene expression by valproate may explain the teratogenicity of this drug. 6 Valproate taken in the daily dose of 1000 mg or more is associated with a higher teratogenic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that VPA induces apoptosis and neural tube defects in postimplantation embryos [100] . A severe foetal valproate syndrome has also been documented [101] . Experimental studies also support the effect of VPA on reprogramming and intrauterine development [102,103] …”
Section: Epigenetic Characteristics Of Valproic Acidmentioning
confidence: 95%
“…Major limitations of presently available studies on neurotoxicity, both developmental and general, include the following aspects:

Relatively few clinical and epidemiological data are available (Smirnova et al 2014). Well-accepted exceptions are tragic events such as the large-scale methylmercury poisoning in Minamata (Ekino et al 2007) or the identification of the fetal valproate syndrome because of the widespread treatment of pregnant epileptic patients with valproic acid (Ozkan et al 2011; Smith and Whitehall 2009);

Neurotoxicity is typically not characterized by cytotoxicity (i.e., neuronal cell death), but rather by impact of toxicants on connectivity, structure, and function of the nervous system during development or at maturity (Giordano and Costa 2012);Extrapolation of data from animal experiments to the human situation may be challenging due to interspecies differences (“humans are no 70 kg mice” (Leist and Hartung 2013);In vitro studies on neurotoxicity usually use transformed or cancer cell lines, which have a response pattern significantly different from normal cells (Kadereit et al 2012; Stiegler et al 2011).
…”
Section: Introductionmentioning
confidence: 99%
“…Well-accepted exceptions are tragic events such as the large-scale methylmercury poisoning in Minamata (Ekino et al 2007) or the identification of the fetal valproate syndrome because of the widespread treatment of pregnant epileptic patients with valproic acid (Ozkan et al 2011; Smith and Whitehall 2009);…”
Section: Introductionmentioning
confidence: 99%